The populist rhetoric as a threat to human rights in Europe: stance of the supranational institutions - Avilés-Hernández, Elena (My University, 2019)
The populist rhetoric that is taking place since not many years ago in some countries around the world, has only accentuate the social divisions and self-segregation of certain minority groups that have seen their rights violated as a consequence of a new concept of security. This debate, as a undeniable sign of the rising concern for both national and international security, does not justify the restriction of their fundamental rights. The groups that are being victims of this situation, in the case of European countries, are mainly foreigners and minorities, which are perceive as a threat to social cohesion and social order, a perception which has been radicalised through out the content of the media and social networks. This situation is part of a backdrop of growing tensions, religious extremism and violent radicalism which, in many cases, is used by the government's own elite to support legislative changes or to justify arbitrary interventions; thus allowing the restriction of fundamental rights in a legitimate way and dehumanizing certain categories of persons believed to be less equal, in order to promote some actions based on hatred and violence. However, this situation is not only happening in Europe, but there are also some other countries that have suffering similar situations. The Philippines example could be used to illustrate the above: During President Rodrigo Duterte's campaign against drugs, the own government was the main character who promoted hatred and violence since it was urging the police and citizens to kill drug dealers and drug users as a way to preserve the national security.
Keywords: Populismo; Migración; Derechos humanos; Congresos y conferencias; Terrorismo transnacional; Vulneración de derechos humanos